2016
DOI: 10.1111/bph.13514
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin induces browning of white adipose tissue and counters obesity by activating TRPV1 channel‐dependent mechanisms

Abstract: BACKGROUND AND PURPOSEThe growing epidemic of obesity and metabolic diseases necessitates the development of novel strategies to prevent and treat such diseases. Current research suggests that browning of white adipose tissue (WAT) promotes energy expenditure to counter obesity. Recent research suggests that activation of the TRPV1 channels counters obesity. However, the mechanism by which activation of TRPV1 channels counters obesity still remains unclear. EXPERIMENTAL APPROACHWe evaluated the effect of dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
251
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(265 citation statements)
references
References 90 publications
8
251
0
6
Order By: Relevance
“…We have previously reported that TRPV1 activation caused beiging of inguinal WAT 9 . This report provides evidence for the expression of TRPV1 protein in BAT and demonstrates that CAP counters diet-induced obesity by activating TRPV1 in BAT.…”
Section: Discussionmentioning
confidence: 90%
“…We have previously reported that TRPV1 activation caused beiging of inguinal WAT 9 . This report provides evidence for the expression of TRPV1 protein in BAT and demonstrates that CAP counters diet-induced obesity by activating TRPV1 in BAT.…”
Section: Discussionmentioning
confidence: 90%
“…58,63,64) Because it would be difficult for dietary intake of capsaicin directly to activate TRPV1 expressed in adipose tissue, these phenotypes might be caused via mechanisms other than TRPV1 expression in adipose tissue. Rather, TRPV1 expressed in peripheral sensory neurons derived from the nodose ganglion is more important for controlling energy metabolism (see also references from Saito et al 65) and Uchida et al…”
Section: Role Of Thermo-sensitive Trp Channels In Adipose Tissuementioning
confidence: 99%
“…The effect of capsaicin/capsinoid treatment has been compared to that of chronic cold exposure, in which sympathetic stimulation results in the activation of BAT [87]. Similarly to the aforementioned curcumin, capsaicin binds to the intestinal transient receptor potential vanilloid 1(TRPV1) receptor, also referred to as the capsaicin receptor, thereby launching the sympathetic response observed with treatment [89]. Surprisingly, capsaicin has also been proven to be harmful to humans and these harmful effects are mediated, in part, by the capsaicin receptor, TRPV1 [9092].…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%